Short-term exposure to carbaryl and UV radiation increases the reproduction output of the collembolan Folsomia candida - Cardoso, Diogo F. N.
Purpose: Ecotoxicological risk assessment of chemical compounds is considered more accurate when mixtures of chemicals and/or interactions between chemicals and natural stressors are considered. To further simulate natural conditions, under which organisms are often exposed to combinations of natural and anthropogenic stressors, the combined exposure of a widely used insecticide, carbaryl, under UV radiation was evaluated. It is more than likely that soil organisms are confronted with a combination of chemical exposure and increasing UV irradiance on the terrestrial habitat. Considering the heterogeneity of contamination in field soils and the probability of collembolan to avoid contaminated soil (less time under exposure), combined effects of carbaryl and ultraviolet radiation were evaluated, by using a short exposure to Folsomia candida. Materials and methods: Single exposures to carbaryl and UV radiation were performed, and adult mortality and number of laid and hatched eggs were reported. Following the results, a combined exposure was carried out, using the same conditions performed previously in the single tests. Organisms were exposed simultaneously to carbaryl (from 1 to 7 mg kg-1) and UV doses (from 1,121.29 to 3,795.26 J m-2), the last corresponds to 1 to 4 h of exposure. Mortality was reported, and organisms were left to lay eggs in culture boxes. Results and discussion: Both ultraviolet radiation and high concentrations of carbaryl as single stressors increased the number of produced eggs of F. candida, with significant differences at higher concentrations (4, 5.5, and 7 mg kg-1) of carbaryl and an EC50 of 5.93 mg kg-1. In the case of UV radiation, statistical differences were found at all concentrations compared with control, with an EC50 of 1,248.24 J m-2. In both cases, no significant mortality was observed. When combined, both stressors acted independently on egg production, showing additivity of effects (independent action (IA) model to data on laid eggs; SS = 0.00056; r2 = 0.75; p < 0.05). Conclusions: This study highlights the importance of taking UV exposure conditions into account when assessing the impact of pesticides to soil biota and looking for more realistic scenarios while showing that soil sheltering occurs only up to a certain extent and that indirect effects can be observed. The opposite trends on responses obtained under standardized tests and short exposures to carbaryl provided some insight on the possible effects of carbaryl during collembolan life cycle.